2018
DOI: 10.4103/ams.ams_140_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the different biomaterials used in alveolar cleft defects in children

Abstract: The aim of this study was to use a literature review to evaluate and compare the different biomaterials used in surgeries for the closure of the palatal and alveolar clefts as alternatives to isolated autografting. For the search strategy, the PubMed and Medline databases were used with the indexing terms “’cleft palate’ (Mesh), ‘biocompatible materials’ (Mesh), and ‘dentistry’ (Mesh).” There was no restriction on language or publication time. After the research, 26 articles were found, and then, only the filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For small oral bone defects alloplastic and xenogenic materials are well established, but for congenital and critical size defects the clinical results of these materials are currently not sufficient (Feinberg et al, 1989). Hence, there are great efforts to develop bone grafts, which can be used for the reconstruction of critical size defects like alveolar clefts (Silva Gomes Ferreira et al, 2018). The bone grafts should have the following characteristics: osteoconductivity, mechanical stability, promotion of vascular ingrowth and stem cell recruitment, and progressive resorption during the replacement by native tissue (Hutmacher et al, 2007;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For small oral bone defects alloplastic and xenogenic materials are well established, but for congenital and critical size defects the clinical results of these materials are currently not sufficient (Feinberg et al, 1989). Hence, there are great efforts to develop bone grafts, which can be used for the reconstruction of critical size defects like alveolar clefts (Silva Gomes Ferreira et al, 2018). The bone grafts should have the following characteristics: osteoconductivity, mechanical stability, promotion of vascular ingrowth and stem cell recruitment, and progressive resorption during the replacement by native tissue (Hutmacher et al, 2007;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that combining autogenous bone with deproteinized bovine bone or β- tricalcium phosphate significantly reduced the need for harvesting bone from the iliac crest, minimized patient morbidity and hospitalization. On the other hand, the use of bovine hydroxyapatite alone resulted in lower bone density compared to that achieved with autogenous bone 15 .…”
Section: Discussionmentioning
confidence: 88%